2011
DOI: 10.1177/0020715211405417
|View full text |Cite
|
Sign up to set email alerts
|

Protest events in international press coverage: An empirical critique of cross-national conflict databases

Abstract: The empirical analysis of protest events and other expressions of social conflict is one of the core tasks of the discipline of comparative sociology. The numerous international data sets and empirical country comparisons that rely exclusively on reporting in English-language newspapers such as The New York Times in surveying protest events nevertheless suffer from considerable distortions. Using the example of some 1800 protest events in Argentina, Mexico and Paraguay in the year 2006, the present study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 27 publications
1
46
0
1
Order By: Relevance
“…The estimates in newspapers therefore are not as haphazard as their lack of methodological reporting would suggest. Second, CCC generates its data by accepting submissions of protest reports instead of managing a team of researchers; adopting this open-source approach means it includes a broader range of sources than most event datasets (Herkenrath and Knoll 2011;Nam 2006).…”
Section: Why Does It Work?mentioning
confidence: 99%
“…The estimates in newspapers therefore are not as haphazard as their lack of methodological reporting would suggest. Second, CCC generates its data by accepting submissions of protest reports instead of managing a team of researchers; adopting this open-source approach means it includes a broader range of sources than most event datasets (Herkenrath and Knoll 2011;Nam 2006).…”
Section: Why Does It Work?mentioning
confidence: 99%
“…The selection of data sources for political violence can be troublesome (LaFree and Dugan 2007;Olzak 2006). Research has shown that databases limited to international media reports do not provide adequate representation across the globe (Herkenrath and Knoll 2011). Fortunately, a more detailed and comprehensive database on incidents of terrorism has recently become available.…”
Section: Dependent Variablementioning
confidence: 99%
“…the number of participants) (Barranco and Wisler 1999;McCarthy et al 1996;Mueller 1997a;Oliver and Myers 1999;Fillieule 1998;McCarthy et al 2008;Herkenrath and Knoll 2011); (2) the geographic distance between the event and the media source, especially its reporting market and audience (Barranco and Wisler 1999;Hocke 1998;McCarthy et al 1996;Mueller 1997a;Fillieule 1998;Strawn 2008;Herkenrath and Knoll 2011); (3) Paralleling these general patterns for events, Amenta et al (2009) find that New York Times mentions of social movement families are greater for larger, better organized and disruptive movements that use protest and those with an enforced governmental policy in place. They also find that the power of partisan allies does not influence selection.…”
Section: Regional Newspaper Reportage In Mexicomentioning
confidence: 98%